Praktik Government Public Relations Paska Otonomi Daerah, Sebuah Tinjauan dengan Kasus Penyuluh KB Sebagai Government Public Relations Bidang KB - Aizirman Djusan (BPSDMP Kominfo Jakarta, 2012)
Multidimentional crisis that occurred in the late 1990s in Indonesia, has influenced the government management. In the national level, it appeared a legal freedom of the press, and changes on government Public Relations institution. While in the level of local government, it was applied a regional autonomy through the Law No.22/1999. These changes also affected other sectors of management, including Public Relations, which in government practice is called Government Public Relations. It beared paradigm shifting in the field of Public Relations after 1999, as well as the challenges on Government Public Relations practice due to the implementation of decentralization. Krisis multidimensional yang terjadi akhir tahun 1990-an di Indonesia, telah mempengaruhi manajemen pemerintahan Indonesia. Pada skala nasional, terjadi legalitas kebebasan pers dan berpendapat, serta perubahan institusi Public Relations pemerintahan. Sementara pada level pemerintahan daerah, diberlakukan penyelenggaraan otonomi daerah melalui Undang-Undang No.22/1999. Perubahan-perubahan tersebut ikut mempengaruhi sektor penyelenggaraan lainnya, termasuk bidang Public Relations, yang dalam pemerintahan disebut Government Public Relations(Humas Pemerintah). Terjadi pergeseran paradigma bidang Public Relations setelah tahun 1999, serta tantangan praktik Government Public Relationsakibat implementasi desentralisasi.